FORMATION OF PROFESSIONAL COMPETENCE OF UNIVERSITY STUDENTS IN THE PROCESS OF PROJECT-ORIENTED TRAINING IN MICROWORKS PROGRAMMING - Nurbekova Ж.К.; Толғанбайұлы, Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
This article presents the key competencies for an IT specialist, which are formed during project-oriented training during the programming of microrobots. A pedagogical experiment was carried out using this technique when studying the programming of microrobots at the Faculty of Information Technology (L.N. Gumilyov ENU). The project was selected taking into account the characteristics of the basic components of the microrobots. As the training platform, we chose the Arduino microcontroller. The study identified the basic requirements for aspiring candidates for positions in the IT industry on the HeadHunter website. Also, based on the OECD (Organization for Economic Co-operation and Development) documents and our own research, an IT specialist development map was developed. This map shows the main positions of the IT industry. The individual development map of each IT specialist is unique, while it was interesting to highlight certain patterns and bring them into our scheme.